High-Temperature Defect Assessment for a P91 Reheat Elbow Using FAD and TDFAD Methods. (2015) - Li, Y.X.; Wen, J.F.; Wang, W.; Zhong, W.L.; Chen, J.
Abstract: Components like elbows operating at high temperature in power and petro-chemical industry are vulnerable to failure of crack growth or net section rupture due to a change in geometry or in mode of loading. In this paper, a P91 reheat elbow subjected to internal pressure of 4.63 MPa at 569 °C for 62, 952 h in service with a part-through-wall crack located at the outer surface is considered. Prediction of whether the elbow can be used for the next ten years is made. First, the procedure provided by Annex U of BS7910-2005 is employed to conduct the high-temperature defect assessment. And in this assessment, the margin against creep damage, margin against fast fracture evaluated by failure assessment diagram (FAD) and the concept of creep crack propagation are employed to estimate its safety in service. Then, a simplified assessment based on the concept of time dependent failure assessment diagram (TDFAD) is conducted. The advantage of TDFAD method is that the risk of creep rupture can be demonstrated directly by the location of assessment point on the diagram avoiding the calculation of C* . Results obtained by using the two methods are compared with each other and have both indicated that the elbow with particular crack defect can be safely operated for another ten years after the crack was discovered.